Biotemplated synthesis of mesoporous silica for doxycycline removal. Effect of pH, temperature, ionic strength and Ca2+ concentration on the adsorption behaviour - Brigante, Maximiliano Eduardo (2016)
Mesoporous silica (SiO2) materials were synthesized in acidic media, using tetraethyl orthosilicate as silica precursor and the water-soluble biopolymer hydroethyl starch (HES) as template, in order to evaluate the effect of temperature synthesis on the morphology and pore structure of synthesized materials. The results show that the mentioned parameters can be tuned by changing the temperature, i.e., from slices with worm-like mesopores of around 5 nm to microporous lamellas when the temperature synthesis increases from 60 °C to 100 °C, respectively. The changes are attributed to a (partial) degradation of the template that hinders the gel formation and disturbs its interaction with the silica species through H-bonds formations and/or electrostatic interactions. The synthesized solids were evaluated as adsorbent of the antibiotic doxycycline (DC) at several values of pH, temperature, ionic strength and Ca2+ concentration. The adsorption of DC strongly increases as pH and ionic strength decrease due to electrostatic attractions and H-bond formations between the functional groups of the antibiotic and the silica active sites. The presence of calcium ions strongly increases the adsorption of DC at pH > 4.4 due to the formation of ternary DC-Ca2+-SiO2 complexes by calcium-bridging. However, Ca2+ concentrations higher than 10-3 M cause the DC precipitation at pH 7 or higher. The analysis of thermodynamic parameters suggests that the adsorption of DC on SiO2 is exothermic and spontaneous in nature. The effect of the tetracycline structure on the adsorption capacity of the synthesized material was also evaluated and discussed.